If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + 17 = -1 Reorder the terms: 17 + 6a = -1 Solving 17 + 6a = -1 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 6a = -1 + -17 Combine like terms: 17 + -17 = 0 0 + 6a = -1 + -17 6a = -1 + -17 Combine like terms: -1 + -17 = -18 6a = -18 Divide each side by '6'. a = -3 Simplifying a = -3
| -2(2x+5)=-2+4x | | .27=x*75 | | x+.07x=15877 | | (4x+8y^2)(x-y^2)=0 | | 5h+21=11 | | W-19=6+9w | | 4(-4x+6)=-6(1+2x)-x | | X+x*4-144=0 | | -p+5=25-6p | | -5(k-3)=-90 | | 3g+17=5 | | .75*80= | | 2-x=-5(x-2) | | 4f-3=13 | | -3+2x=-(4-x) | | 2sin(x)-3=-2 | | 5d-7=23 | | 7=2x^2+6x+7 | | -3(5+3x)=4x-2 | | B+8=1 | | -.7x+26.9=-x+29 | | 10-x+6x=-x-4x | | -22=-6+k | | 24+8x=40 | | X^2+kx-k+8=0 | | -22=-6+6 | | 3(x+6)=2(3x+15) | | -7x+26.9=-x+29 | | 1in=6ft | | 10(b-8)-4+3b= | | 3c-1=20 | | 6+3x=-12-4x |